Protection of Bank Deposits through Securing Bank Capital (Al-Mansour Journal, 2026)
This research addresses the protection of bank deposits through securing bank capital, considering that bank capital represents one of the most important legal and financial mechanisms that contribute to strengthening the stability of banking institutions and ensuring their ability to fulfill obligations towards depositors. The importance of this topic has increased in light of the financial and economic risks facing the banking sector, which may affect the capacity of banks to safeguard depositors’ funds and maintain financial stability.The study analyzes the legal and regulatory framework governing bank capital and capital adequacy requirements, highlighting their role in strengthening the financial soundness of banks and reducing the risks of bank insolvency. It also examines several mechanisms that support bank capital, including capital increases, banking reserves, risk management systems, credit and investment policy controls, as well as compliance with banking governance standards and financial disclosure requirements. In addition, the research discusses the role of deposit guarantee systems in enhancing confidence in banking institutions.The study concludes that securing bank capital constitutes a fundamental pillar for the protection of bank deposits and the achievement of financial stability. Strong capital bases enhance banks’ ability to absorb financial shocks and manage risks effectively, while also strengthening depositor confidence in the banking system. The research ultimately presents several findings and recommendations aimed at improving the legal and regulatory framework governing bank capital in order to enhance depositor protection and ensure the stability of the banking system.
Keywords: Bank Deposits; Bank Capital; Capital Adequacy; Financial Stability; Bank Supervision.